The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31234/osf.io/yjfg3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mask exposure during COVID-19 changes emotional face processing

Abstract: Faces are one of the key ways that we obtain social information about others. They allow people to identify individuals, understand conversational cues, and make judgements about other’s mental states. When the COVID-19 pandemic hit the United States, widespread mask-wearing practices were implemented, causing a shift in the way Americans typically interact. This introduction of masks into social exchanges posed a potential challenge – how would people make these important inferences about others when a large … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Similarly, previous studies showed that individual differences in mask exposure influenced the use of visual cues from the face. A longitudinal study (two controlled experiments with 6 months apart) assessed the perceived emotional similarity between a pair of unmasked faces (Barrick et al, 2020). As mask exposure increases, there is an increase in the eye cue use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, previous studies showed that individual differences in mask exposure influenced the use of visual cues from the face. A longitudinal study (two controlled experiments with 6 months apart) assessed the perceived emotional similarity between a pair of unmasked faces (Barrick et al, 2020). As mask exposure increases, there is an increase in the eye cue use.…”
Section: Discussionmentioning
confidence: 99%
“…An examination of eye movements showed that while Western individuals' eye fixations were scattered evenly across the faces, Eastern individuals mainly focused on the eyes (Jack et al, 2009). In addition, there is research that demonstrates that as individuals' exposure to masks increases, they actually get better at reading emotions (Barrick et al, 2020). Hence, timing of execution of these studies may matter.…”
Section: Significance Statementmentioning
confidence: 99%
“…Thus, when encountering a facial expression of forward facing, direct eye-gaze fear, the typically encountered signature of that expression is less cogent, leading to diminished detection accuracy (Adams & Kleck, 2003;Im et al, 2017;Sato et al, 2004). The effects of introducing noise to facial expression decoding can also be seen in recent research that suggests wearing a mask (hiding signal from the mouth) diminishes individuals' reliance on arousal cues (Barrick et al, 2020). Future research should investigate how obfuscation of face parts, gaze and head positioning influence accuracy of emotional expression identification when only low or high spatial frequency information is available.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Some emotional expressions including happy, sad, and angry are sometimes not perceived at all under a mask, with the face being interpreted instead as neutral ( Carbon, 2020 ). However, consistently engaging in social interaction with masked individuals is already leading to behavioral adaptation in Americans, with those who have more frequent masked interactions increasingly using cues for visual emotion information from the eyes ( Barrick et al., 2020 ).…”
Section: Main Textmentioning
confidence: 99%